Comparative total phenolic content, anti-lipase and antioxidant activities of two Nigerian aframomum species (2016)
The anti-obesity drug development is presently not a bright story. So far, drugs reported to be effective have stimulated controversies due to side effects they elicit. Obesity and its co-morbidities continue however to constitute major problems in both developed and developing countries. This has resulted in a continuous search for novel, cost-effective, safe and potent alternatives. This study investigated the ethanolic extracts of two Nigerian Aframomum species for their anti-lipase and anti-oxidant activities as well as estimates of their polyphenol contents. Lipase activity was determined using glyceryltrioleate emulsion as a substrate and measuring the release rate of oleic acid from it. Percentage inhibition of lipase by the methanolic extracts of plants was determined spectrophotometrically at T€ and Tƒ € (30 minutes after incubation at 37ÚC). DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging activity of the extracts and that of gallic acid as control was measured using the stable radical DPPH method and absorbance at 515 nm using a spectrophotometer. The IC50 (half-maximal inhibitory concentration) value was calculated by linear regression analysis and the total phenolic content was determined by the Folin-Ciocalteau method at 765 nm. The standard curve was prepared by solutions of Gallic acid in methanol: water (50:50, v/v). Total phenol values are expressed in terms of Gallic acid equivalent (w/w of dry mass). Aframomum melegueta exhibited the highest phenolic content of 60.4 ± 2.36 mgGAE/g, a percentage antioxidant activity of 86.6 % at 200µg/ml and percentage lipase inhibition of 89% at 1mg/ml while Aframomum danielli revealed a total phenolic content of33.3 ± 2.71mgGAE/g, a percentage antioxidant activity of 77.3% at 200µg/ml and percentage lipase inhibition of 73% at 1 mg/ml. The result provides some justifications for the use of these plants in ethno-medicine for the management of obesity. The species exhibited properties that are beneficial to health and therefore could find use as an alternative and/or complementary strategy in managing associated co-morbidities of obesity, and also as possible template for future anti-obesity drug development.